(3GdGjVGM hGdJHUjQ aj GHGfI aVd jhe GdZOjQs - (3CHh eMeO GdMSf Hf Ydj Hf eMeO Hf GdMSf GdLhgQj GdebfYjs
(3ChdgG (B:s
(3GdMeO ddg eaVd GhdjGAg HGJHGY GFeI GdMb JaVjdkG s
(3BNQgG (B:s
(3EdG ai GdfHhI hSGhGg Ydi Hf CHj WGdH GdPi MVQJ ef aVGFdg GdGahGg hcdf Yf fYJ efGbHI GdGeS hGdTaGg JeJ s
(3HgG fXGe GdJYbjHIs
(3hcJHJ ai YUQ CHj GdWjH eMeO HQgGf GdOjf GdebOS YHO GdbGOQ fLe GdOjfs
(3hHBNQg eLGdS ai aVd UGMH jhe GdZOjQ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs